A experimentação das vanguardas brasileiras no pós-guerra: conceito e materialidade - Maria Alice Honório Sanna Castello Branco (2019)
From the perspective of the Preservation of Cultural Heritage research line of this Graduate Programe, this thesis deals with the materials and technical strategies employed in the construction of paintings of constructive movements of the Brazilian avant-garde, performed during the 1950s, by artists who worked in the Rio and São Paulo. The main objective of this study is to analyze the materiality and the technical specificities required by the geometric proposal of concrete and neoconcrete languages in the construction of works of art, considering that the (re-) knowledge of material and technical aspects is essential for making decisions that can guarantee the preservation of these works of modern art. This study was carried out from a set of twenty representative works of these languages produced between 1952 and 1961 by Waldemar Cordeiro (1925-1973), Luiz Sacilotto (1924-2003), Judith Lauand (1922-) and Hermelindo Fiaminghi (1922-2004) ), members of the Ruptura group, from São Paulo; and of Lygia Pape (1927-2004), Aluísio Carvão (1920-2001) and Hélio Oiticica (1937-1980), of the Frente de Rio de Janeiro group, besides Willys de Castro (1926-1988), who joined these last in 1959, from the Neoconcrete Movement. The methodology of the research supported in the field of the Technical Art History assumes the use of the methodological bases of the Art History and the Conservation Science for the structuring of knowledge related to the technology of construction of the selected works. Thus, the observations and analyzes made through the intersection between the formal analysis and the scientific examinations structured from organoleptic studies, scientific documentation by image, and physical-chemical analyzes made, respectively, by the teams of the Laboratory of Conservation Sciences (LACICOR) and the Laboratory of Scientific Documentation by Image (iLAB), both linked to the Conservation and Restoration Center (CECOR) of the School of Fine Arts of UFMG. Also, it was associated to historical studies from historiographic research that allowed an extended view of the artistic object from the indissociated perception between concept and materiality. In addition to this methodological basis, the research included interviews with Judith Lauand - one of the exponents of the concrete movement still alive - as well as a cast of people who had the opportunity to live with the selected artists. Thus, through the sharing of their memories and records, these interviews could elucidate some issues, such as those related to the use of materials and the use of techniques that shaped the production process and the creation of each artist in the atelier. The main value of this thesis is linked to the transdisciplinary methodology, because, when accessing the works researched from the Technical Art History - an innovative field of knowledge in Conservation Science -, focusing on the conditional relationship between the creation process, the aesthetic condition, and the technology of construction of a work of art, it expands the intrinsic relations between materiality and the concept. In the same way, the study of the works of art of this period from the connection between the artistic concepts expressed in the artistic circuit and the construction technology of the works carried out expands the principle of approximation towards the art object, contributing to a curatorial and subsidized conservation. The period established for this study comprises the 1950s, considering the impact of the process of industrialization and modernization on Brazilian society, from the postwar period on the art system, together with the establishment of the paradigms of Concrete and Neoconcrete art produced in Brazil through artistic movements.